Comprehensive profiling of 1015 patients’ exomes reveals genomic-clinical associations in colorectal cancer - Qi Zhao (Nature Communications, 2022)
The ChangKang (Heathy Bowel) project was established to collect molecular and clinical information of a thousand Chinese colorectal cancer patients. Here, the authors present the genomic landscape of the ChangKang cohort and find a subgroup of patients defined by abnormal mitochondrial copy numbers.